Isolation, biological and whole genome characteristics of a Proteus mirabilis bacteriophage strain - Xirui Hao; Xin Cen; Min He; Yongping Wen; Huanrong Zhang (BMC Microbiology, 2023)
Abstract Proteus mirabilis, a naturally resistant zoonotic bacterium belonging to the Enterobacteriaceae family, has exhibited an alarming increase in drug resistance. Consequently, there is an urgent need to explore alternative antimicrobial agents. Bacteriophages, viruses that selectively target bacteria, are abundant in the natural environment and have demonstrated potential as a promising alternative to antibiotics. In this study, we successfully isolated four strains of Proteus mirabilis phages from sewage obtained from a chicken farm in Sichuan, China. Subsequently, we characterized one of the most potent lytic phages, Q29, by examining its biological and genomic features. Comparative genomic analysis revealed the functional genes and phylogenetic evolution of Q29 phages. Our findings revealed that Proteus mirabilis bacteriophage Q29 possesses an icosahedral symmetrical head with a diameter of 95 nm and a tail length of 240 nm. Moreover, phage Q29 exhibited stability within a temperature range of 37 ℃ to 55 ℃ and under pH conditions ranging from 4 to 9. The optimal multiplicity of infection (MOI) for this phage was determined to be 0.001. Furthermore, the one-step growth curve results indicated an incubation period of approximately 15 min, an outbreak period of approximately 35 min, and an average cleavage quantity of approximately 60 plaque-forming units (PFU) per cell. The genome of phage Q29 was found to have a total length of 58,664 base pairs and encoded 335 open reading frames (ORFs) without carrying any antibiotic resistance genes. Additionally, genetic evolutionary analysis classified phage Q29 within the family Caudalidae and the genus Myotail. This study provides valuable research material for further development of Proteus mirabilis bacteriophage biologics as promising alternatives to antibiotics, particularly in light of the growing challenge of antibiotic resistance posed by this bacterium.